DAMPAK RADIKALISME ATASNAMA AGAMA BAGI KEHIDUPAN MASYARAKAT SECARA LUAS - Sudi Raharjo (LPPM Universitas Pekalongan, 2022)
This study aims to discuss radicalism in the name of religion and its impact on life in society at large. This research method is descriptive qualitative through library research study. The results and discussion of this research include the notion of radicalism, the impact of radicalism, and the notion of radicalism in the name of religion in social life. This lesson concludes that not all violence that occurs in society can be called radicalism, but it depends on each person's understanding in responding to it. This study recommends to everyone that in order to achieve social or political change one does not have to use violence especially violence in the name of religion that leads to acts of terrorism.